A pilot study: bovine colostrum supplementation and hormonal and autonomic responses to competitive cycling - Shing, C. M.; Peake, J. M.; Suzuki, K.; Jenkins, D. G.; Coombes, J. S. (The Journal of Sports Medicine and Physical Fitness, 2013)
Aim: The aim of this pilot investigation was to examine the influence of bovine colostrum protein concentrate (CPC) supplementation on salivary hormones, salivary IgA and heart rate variability over consecutive days of competitive cycling. Methods: Ten highly-trained male road cyclists (mean±SEM; age=22.2±4.7 yr; mass=70.5±4.5 kg; VO2max=72.9±3.8 mL.kg-1.min-1) were randomly assigned to a control (N.=6, 10g whey protein concentrate/day) or bovine CPC group (N.=4, 10 g bovine CPC/day). Cyclists provided a baseline saliva sample before commencing eight weeks of supplementation, and competing in a five day cycle race. Cyclists provided saliva samples and measured heart rate variability (HRV) each day of the race. Saliva samples were analysed for cortisol, testosterone and IgA concentrations. Results: Bovine CPC supplementation was associated with increased morning cortisol concentration on the first day of racing when compared to the control group (P=0.004) and significantly prevented a decrease in testosterone concentration over the race period (P=0.05). Across the race period parasympathetic indices of HRV were elevated in the bovine CPC group and reduced in the control group (P=0.05), while there were no significant differences in salivary IgA between groups. Conclusion: Bovine CPC supplementation maintained salivary testosterone concentration and modulated autonomic activity over consecutive days of competitive cycling. This pilot study provides justification to explore the effects of bovine CPC on recovery in endurance athletes further.